2022
DOI: 10.3233/jad-220118
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Functional, and Emotional Changes During the COVID-19 Pandemic in Greek Patients with Neurocognitive Disorders

Abstract: Background: Prolonged periods of social deprivation, such as COVID-19-related lockdowns, are associated with deleterious effects on cognitive functions. Objective: The aim of this study was to gauge the effect of prolonged social isolation on the cognitive function of older adults with neurocognitive disorders. Methods: We recruited 125 older adults with minor or major neurocognitive disorders divided into two groups. The control group was tested at the first period of the study (October 2018–May 2019), wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Thus, it was expected that it would immediately impact the population as a whole with severe psychological and cognitive implications. Indeed, our findings are in line with previous literature on COVID-19 which report the presence of cognitive decline in the short [ 20 , 42 , 53 ], medium [ 49 , 52 , 61 ], and long-term periods [ 50 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it was expected that it would immediately impact the population as a whole with severe psychological and cognitive implications. Indeed, our findings are in line with previous literature on COVID-19 which report the presence of cognitive decline in the short [ 20 , 42 , 53 ], medium [ 49 , 52 , 61 ], and long-term periods [ 50 , 92 ].…”
Section: Discussionsupporting
confidence: 93%
“…During the medium and long period of COVID-19 lockdown measures, all groups of neurological patients exhibited a significant decline in functional and cognitive status compared to the pre-COVID period. During the medium period (5 to 8 months), three out of four studies showed adverse effects of COVID-19 lockdown measures on attention [ 46 ], and on the overall patients’ cognitive status [ 48 , 49 ], except for Ref. [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous cross-sectional studies in different countries have investigated the impact of the COVID-19 pandemic and social-distancing measures on neuropsychiatric symptoms of AD. They consistently demonstrated that the COVID-19 pandemic and related restrictions lead to the worsening of neuropsychiatric symptoms in AD patients [ 5 , 7 , 114 , 115 ], with most pronounced neuropsychiatric symptoms being agitation, anxiety, and depression. The worsening of irritability, sleep disturbance, apathy, aberrant motor activity, appetite disturbances, and delusion were also reported in some of these studies.…”
Section: Covid-19 and Admentioning
confidence: 99%
“…These data are consistent with another longitudinal 1-year follow-up study [ 7 ], which reported that the decline of MMSE scores in AD patients during the pandemic was similar to the rate of yearly decline in previous studies before the pandemic [ 7 ]. On the contrary, Tsiakiri et al longitudinally assessed the cognitive performance of 21 AD patients during 7-month follow-up that corresponded to the strict lockdown period in Greece [ 115 ]. They found significantly greater worsening of MMSE and MoCA scores in AD patients during the COVID-19 pandemic lockdown compared to the AD controls who completed follow-up before the lockdown.…”
Section: Covid-19 and Admentioning
confidence: 99%
“…There is a strong relationship between depression and physical and emotional quality of life in stroke survivor–caregiver dyads. 141 Better caregiver preparedness can reduce the likelihood of depression and overall improve the quality of life of the stroke survivor–caregiver dyad. 142 Caregivers who have better caregiver preparedness are less likely to suffer from mood disturbances, experience lower burden of care, and perform better self-care.…”
Section: Family and Caregiver Picsmentioning
confidence: 99%